A new sauropodomorph ichnogenus from the Lower Jurassic of Sichuan, China fills a gap in the track record. (2nd October 2016) - Xing, Lida; Lockley, Martin G.; Zhang, Jianping; Klein, Hendrik; Li, Daqing; Miyashita, Tetsuto; Li, Zhongdong; Kümmell, Susanna B.
Abstract : A dinosaur tracksite in the Lower Jurassic Ziliujing Formation of Sichuan Province, China consists of a spectacular sub-vertical exposure, with multiple track-bearing levels and trackways showing parallel and bimodal orientations. Based on well-preserved material, the new ichnogenus and ichnospecies, Liujianpus shunan ichnogen. nov. ichnosp. nov. is erected to accommodate distinctive sauropodomorph trackways occurring in this assemblage. Liujianpus has a unique combination of features, some relating to the early Jurassic basal sauropodomorph (prosauropod in traditional usage) ichnogenus Otozoum, others to the sauropod ichnogenus Brontopodus . Despite such a mix of basal sauropodomorph- and sauropod-like features, the trackmaker of Liujianpus is likely a basal sauropodomorph. This identification is consistent with the occurrence of basal sauropodomorph skeletons from geographically and chronologically close localities. The other distinct morphotype from the tracksite is linked to a sauropod trackmaker. As such, the ichnofauna consisting of two distinct foot morphotypes reflects the diversity of sauropodomorph dinosaurs in the Early Jurassic of Asia.